Training the 21st Century Police Officer Redefining Police Professionalism for the Los Angeles Police Department - Glenn, Russell W. (RAND Corporation, 2003)
Restructure the LAPD Training Group to allow the centralization of planning; instructor qualification, evaluation, and retention; and more efficient use of resources.